Home My Page Projects Code Snippets Project Openings diderot

# SCM Repository

[diderot] Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml
 [diderot] / branches / ein16 / src / compiler / high-il / normalize-ein.sml

# Diff of /branches/ein16/src/compiler/high-il/normalize-ein.sml

revision 2458, Tue Oct 8 19:42:58 2013 UTC revision 2856, Thu Jan 15 01:42:24 2015 UTC
# Line 5  Line 5
5
6      structure E = Ein      structure E = Ein
7      structure P=Printer      structure P=Printer
8      structure O =OrderEin      structure F=Filter
9      in      structure G=EpsHelpers

(*Flattens Add constructor: change, expression *)
|flatten(i,((E.Const c):: l'))=
if (c>0.0 orelse c<0.0) then let
val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end
else flatten(1,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let
val(b,a)=flatten(i,l') in (b,[e]@a) end

val (b,a)=flatten(0,e)
in case a
of [] => (1,E.Const(1.0))
| [e] => (1,e)
(* end case *)
end

fun mkProd [e]=(1,e)
| mkProd(e)=let
fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
|flatten(i,((E.Const c)::l'))=
if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
else flatten(i,l')
| flatten(i,[])=(i,[])
| flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
val (change,a)=flatten(0,e)
in if(change=3) then (1,E.Const(0.0))
else case a
of [] => (1,E.Const(0.0))
| [e] => (1,e)
| es => (change, E.Prod es)
(* end case *)
end

(*

fun mkEps(e)= (case e
of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)
| E.Apply(E.Partial [E.V a,E.V b], E.Prod( (E.Epsilon(i,j,k))::m ))=>
(if(a=i andalso b=j) then (1,E.Const(0.0))
else if(a=i andalso b=k) then (1,E.Const(0.0))
else if(a=j andalso b=i) then (1,E.Const(0.0))
else if(a=j andalso b=k) then (1,E.Const(0.0))
else if(a=k andalso b=j) then (1,E.Const(0.0))
else if(a=k andalso b=i) then (1,E.Const(0.0))
else (0,e))
|_=> (0,e)
(*end case*))

10
11        in
12
13  fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e      fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
14      of E.Tensor(a,[])=> (0,E.Const(0.0))      val testing=0
15      | E.Tensor _=> (0,E.Sum(c,E.Apply(d,e)))      fun flatProd e =F.rewriteProd e
16      | E.Field _ =>(0, E.Sum(c, E.Apply(d,e)))      fun mkProd e= F.mkProd e
17      | E.Const _=> (1,E.Const(0.0))      fun filterSca e=F.filterSca e
18      | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(d, e))) l))      fun filterField e=F.filterField e
19      | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))      fun mkAdd e=F.mkAdd e
20      | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))      fun filterGreek e=F.filterGreek e
21      | E.Prod[E.Tensor(a,[]), e2]=>  (1, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )      fun testp n=(case testing
22      | E.Prod((E.Tensor(a,[]))::e2)=>  (1, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )          of 0=> 1
23      | E.Prod es =>   (let          | _ =>(print(String.concat n);1)
fun prod [e] = (E.Apply(d, e))
| prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr
in ( E.Add[ a, m] ) end)
| prod _= (E.Const(1.0))
in (1, E.Sum(c,prod es))  end)
| _=> (0,E.Sum(c,E.Apply(d,e)))
24      (*end case*))      (*end case*))
25
26        (*prodAppPartia:ein_exp list * mu list ->ein_exp
27        * chain rule
28     *)     *)
29        fun prodAppPartial(es,p1)=(case es
30            of []      => err "Empty App Partial"
31            | [e1]     => E.Apply(E.Partial p1,e1)
32            | (e1::e2) => let
33                val l= prodAppPartial(e2,p1)
34                val (_,e2')= mkProd[e1,l]
35                val (_,e1')=mkProd(e2@ [E.Apply(E.Partial p1, e1)])
36                in
38                end
39            (* end case *))
40
41        (*mkSum:sum_indexid list * ein_exp->int *ein_exp
42  fun rmEpsIndex(_,_,[])=[]      *distribute summation expression
| rmEpsIndex([],[],cs)=cs
| rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)
| rmEpsIndex(i::ix,rest ,(E.V c)::cs)=
if(i=c) then rmEpsIndex(rest@ix,[],cs)
else rmEpsIndex(ix,rest@[i],(E.V c)::cs)

(* Transform eps to deltas*)
fun epsToDels(E.Sum(count,E.Prod e))= let
fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=
let

(*Function is called when eps are being changed to deltas*)
fun createDeltas(i,s,t,u,v, e3)= let

(*remove index from original index list*)
(*currrent, left, sumIndex*)

val s'= rmEpsIndex([i,s,t,u,v],[],count)
val s''=[E.V s, E.V t ,E.V u, E.V v]
val deltas= E.Sub(
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),
E.Sum(s'',E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3)))

in (case (eps,s')
of ([],[]) =>(1,deltas)
|([],_)=>(1,E.Sum(s',deltas))
|(_,[])=>(1,E.Prod(eps@[deltas]))
|(_,_) =>(1, E.Sum(s', E.Prod(eps@[deltas])))
)
end

in if(a=d) then createDeltas(a,b,c,e,f, e3)
else if(a=e) then createDeltas(a,b,c,f,d, e3)
else if(a=f) then createDeltas(a,b,c,d,e, e3)
else if(b=d) then createDeltas(b,c,a,e,f, e3)
else if(b=e) then createDeltas(b,c,a,f,d,e3)
else if(b=f) then createDeltas(b,c,a,d,e,e3)
else if(c=d) then createDeltas(c,a,b,e,f,e3)
else if(c=e) then createDeltas(c,a,b,f,d,e3)
else if(c=f) then createDeltas(c,a,b,d,e,e3)
else (0,E.Const 0.0)
end
fun findeps(e,[])= (e,[])
| findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)
| findeps(e,es)= (e, es)

fun dist([],eps,rest)=(0,eps,rest)
| dist([e],eps,rest)=(0,eps@[e],rest)
| dist(c1::current,eps,rest)=let
val(i, exp)= doubleEps(c1::current,eps,rest)
in  (case i of 1=>(i,[exp],[E.Const 2.0])
|_=> dist(current, eps@[c1],rest))
end

val (es,rest)=findeps([],e)

in
dist(es,[],rest)
end

fun rmIndex(_,_,[])=[]
| rmIndex([],[],cs)=cs
| rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
| rmIndex(i::ix,rest ,c::cs)=
if(i=c) then rmIndex(rest@ix,[],cs)
else rmIndex(ix,rest@[i],c::cs)

(* Apply deltas to tensors/fields*)
fun reduceDelta(E.Sum(c,E.Prod p))=let

fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
| findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
| findDeltas(dels,rest,es)=  (dels,rest,es)

fun distribute(change,d,dels,[],done)=(change,dels@d,done)
| distribute(change,[],[],e,done)=(change,[],done@e)
| distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
| distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
| distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])

val (dels,eps,es)=findDeltas([],[],p)
val (change,dels',done)=distribute([],dels,[],es,[])
val index=rmIndex(change,[],c)

in
(change, E.Sum(index,E.Prod (eps@dels'@done)))
end

fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(print "apply sum";case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))

| E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
| E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,e1))])

| E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,E.Prod e2))])
(*  | E.Prod es=> (let
fun prod [e1] =E.Apply(E.Partial d,e1)
| prod(e1::e2)=(let
val l= prod(e2) val m= E.Prod[e1,l]
val lr=e2 @[E.Apply(E.Partial d,e1)] val(b,a) =mkProd lr
end)
in (1,prod es) end)*)
|_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
(* end case*))

fun mkApply2(E.Apply(E.Partial d,e))=(print "aa";case e
of E.Tensor(a,[])=>(1,E.Const 0.0)
| E.Const _ =>(1,E.Const 0.0)
| E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
| E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
| E.Apply(E.Partial e1,e2)=>(1,E.Apply(E.Partial(d@e1), e2))
| E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
| E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,e1)])
| E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Prod e2)])
| E.Prod es=> (let
fun prod [e1] =(0,E.Apply(E.Partial d,e1))

| prod(E.Tensor t::e2)=(let
val (change,l)= prod(e2) val m= E.Prod[E.Tensor t,l]
val lr=e2 @[E.Apply(E.Partial d,E.Tensor t)] val(b,a) =mkProd lr
end)
| prod(E.Field f::e2)=(let
val (change,l)= prod(e2) val m= E.Prod[E.Field f,l]
val lr=e2 @[E.Apply(E.Partial d,E.Field f)] val(b,a) =mkProd lr
end)
| prod e = (0,E.Apply(E.Partial d, E.Prod e))
(*)prod (e1::e2)= E.Apply(E.Partial d, E.Prod ([e1]@e2))
43  *)  *)
44        fun mkSum(c1,e1)=(case e1
45          val (a,b)= prod es          of E.Conv _   => (0,E.Sum(c1,e1))
46            | E.Field _   => (0,E.Sum(c1,e1))
47          in (a, b) end)          | E.Probe _   => (0,E.Sum(c1,e1))
48      |_=>(0,E.Apply(E.Partial d,e))          | E.Apply _   => (0,E.Sum(c1,e1))
49            | E.Delta _   => (0,E.Sum(c1,e1))
50            | E.Epsilon _ => (0,E.Sum(c1,e1))
51            | E.Eps2 _    => (0,E.Sum(c1,e1))
52            | E.Tensor(_,[]) => (1,e1)
53            | E.Tensor _  => (0,E.Sum(c1,e1))
54            | E.Neg e2    => (1,E.Neg(E.Sum(c1,e2)))
55            | E.Sub (a,b) => (1,E.Sub(E.Sum(c1,a),E.Sum(c1,b)))
57            | E.Div (a,b) => (1,E.Div(E.Sum(c1,a),E.Sum(c1,b)))
58            | E.Lift e    => (1,E.Lift(E.Sum(c1,e)))
59            | E.Sum(c2,e2)=> (1,E.Sum(c1@c2,e2))
60            | E.Prod p    => filterSca(c1,p)
61            | E.Const 0   => (1,E.Const 0) (*expression could have been changed to 0*)
62            | E.Const _   => err("Sum of Const")
63            | E.Partial _ => err("Sum of Partial")
64            | E.Krn _     => err("Krn used before expand")
65            | E.Value _   => err("Value used before expand")
66            | E.Img _     => err("Probe used before expand")
67      (* end case*))      (* end case*))
68
69  fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(print "in here ";case e      (* mkapply:mu list*ein_exp->int*ein_exp
70      of E.Const _=>(1,E.Const 0.0)      * rewrite Apply
| E.Tensor(_,[])=> (1,E.Const 0.0)
| E.Field _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
| E.Apply(E.Partial e1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@e1),e2)))

| E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
| E.Sub(e2, e3) =>
(*(0,E.Sub(e2,e3))
71                  *)                  *)
72                  (print "sub";(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3)))))      fun mkapply(d1,e1)=(case e1
73            of E.Lift e   => (1,E.Const 0)
74       | E.Prod [e1]=>(print "one";(1,E.Sum(c,E.Apply(E.Partial d,e1))))          | E.Prod []   => err("Apply of empty product")
76            | E.Conv(v, alpha, h, d2)    =>let
77      | E.Prod(E.Tensor(a,[])::e2::[])=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,e2))]))              val E.Partial d3=d1
78                in
79      | E.Prod(E.Tensor(a,[])::e2)=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))]))                  (1,E.Conv(v,alpha,h,d2@d3))

| E.Prod es =>(print "in prod";let
fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
| prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
fun matchprod(2,_,_,_)= 1 (*matched 2*)
| matchprod(num,_,_,[])=0
| matchprod(0,_,_,[eps])=0
| matchprod(num,[],rest,eps::epsx)=
matchprod(num,rest,[],epsx)
| matchprod(num,E.V p::px,rest,eps::epsx)=
if(p=eps) then matchprod(num+1,px,rest,epsx)
else matchprod(num,px,rest@[E.V p], eps::epsx)
| matchprod(num,p::px,rest,eps)=
matchprod(num,px,rest,eps)

val change'= matchprod(0,d,[],[i,j,k])
in (case change'
of 1 => (1,E.Const 0.0)
| _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps)
(*end case*))
80              end              end
81          | prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let          | E.Field _   => (0,E.Apply(d1,e1))
82              fun applyDelPartial([],_)=(0,[])          | E.Probe _   => (0,E.Apply(d1,e1))
83              | applyDelPartial(p::px,r)=          | E.Apply(E.Partial d2,e2)  => let
84                  if(j=p) then (1,r@[i]@px)              val E.Partial d3=d1
else  applyDelPartial(px,r@[p])

val (change',px)=applyDelPartial(d,[])

in (case change'
of 1 => (let val index=rmIndex([j],[],sum)
in prod(1,rest, index,px, ps) end )
| _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)
(*end case*)) end

| prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)

val (change,exp) = prod(0,[],c, d, es)

85          in          in
86              (change,exp)                  (1,E.Apply(E.Partial(d3@d2),e2))
87          end)              end
88          | _=>(print "nope";(0,E.Sum(c,E.Apply(E.Partial d,e))))          | E.Apply _   => err" Apply of non-Partial expression"
89            | E.Sum(c2,e2)=> (1,E.Sum(c2,E.Apply(d1,e2)))
90            | E.Neg e2    => (1,E.Neg(E.Apply(d1,e2)))
92            | E.Sub (a,b) => (1,E.Sub(E.Apply(d1,a),E.Apply(d1,b)))
93            | E.Div (g,b) => (case filterField[b]
94                of (_,[]) => (1,E.Div(E.Apply(d1,g),b)) (*Division by a real*)
95                | (pre,h) => let
96                    (*quotient rule*)
97                    val g'=E.Apply(d1,g)
98                    val h'=E.Apply(d1,flatProd(h))
99                    val num=E.Sub(E.Prod([g']@h),E.Prod[g,h'])
100                    val denom=E.Prod(pre@h@h)
101                    in (1,E.Div(num,denom))
102                    end
103                (*end case*))
104            | E.Prod p =>let
105                val (pre, post)= filterField p
106                val E.Partial d3=d1
107                in mkProd(pre@[prodAppPartial(post,d3)])
108                end
109            | E.Const _   => (1,E.Const 0)(*err("Const without Lift")*)
110            | E.Tensor _  => err("Tensor without Lift")
111            | E.Delta _   => err("Apply of Delta")
112            | E.Epsilon _ => err("Apply of Eps")
113            | E.Eps2 _ => err("Apply of Eps")
114            | E.Partial _ => err("Apply of Partial")
115            | E.Krn _     => err("Krn used before expand")
116            | E.Value _   => err("Value used before expand")
117            | E.Img _     => err("Probe used before expand")
118          (* end case*))          (* end case*))
119
120  (*      (*mkprobe:ein_exp* ein_exp-> int ein_exp
121  E.Sum(c,Apply(d,e))      *rewritten probe
try E.Sum(c,e)=> E.Sum(c',e')
==>    E.Sum(c',E.Apply(d,e'))
E.Apply(d,e')=> E.Apply(d',e'')
==>E.Sum(c',E.Apply(d',e'')
122  *)  *)
123        fun mkprobe(e1,x)=(case e1
124            of E.Lift e   => (1,e)
125            | E.Prod []   => err("Probe of empty product")
126            | E.Prod p    => (1,E.Prod (List.map (fn(a)=>E.Probe(a,x)) p))
127            | E.Apply _   => (0,E.Probe(e1,x))
128            | E.Conv _    => (0,E.Probe(e1,x))
129            | E.Field _   => (0,E.Probe(e1,x))
130            | E.Sum(c,e') => (1,E.Sum(c,E.Probe(e',x)))
132            | E.Sub (a,b) => (1,E.Sub(E.Probe(a,x),E.Probe(b,x)))
133            | E.Neg e'    => (1,E.Neg(E.Probe(e',x)))
134            | E.Div (a,b) => (1,E.Div(E.Probe(a,x),E.Probe(b,x)))
135            | E.Const _   => (1,e1)(*err("Const without Lift")*)
136            | E.Tensor _  => err("Tensor without Lift")
137            | E.Delta _   => (0,e1)
138            | E.Epsilon _ => (0,e1)
139            | E.Eps2 _    => (0,e1)
140            | E.Partial _ => err("Probe Partial")
141            | E.Probe _   => err("Probe of a Probe")
142            | E.Krn _     => err("Krn used before expand")
143            | E.Value _   => err("Value used before expand")
144            | E.Img _     => err("Probe used before expand")
145        (*end case*))
146
147  (*Apply normalize to each term in product list      (* normalize: EIN->EIN
148  or Apply normalize to tail of each list*)      * rewrite body of EIN
149  fun normalize (Ein.EIN{params, index, body}) = let      * note "c" keeps track if ein_exp is changed
150        *)
151        fun normalize (ee as Ein.EIN{params, index, body}) = let
152        val changed = ref false        val changed = ref false

153        fun rewriteBody body = (case body        fun rewriteBody body = (case body
154               of E.Const _=> body               of E.Const _=> body
155                | E.Tensor _ =>body                | E.Tensor _ =>body
156                | E.Field _=> body                | E.Field _=> body
| E.Kernel _ =>body
157                | E.Delta _ => body                | E.Delta _ => body
| E.Value _ =>body
158                | E.Epsilon _=>body                | E.Epsilon _=>body
159            | E.Eps2 _      => body
160            | E.Conv _      => body
161            | E.Partial _   => body
162            | E.Krn _       => raise Fail"Krn before Expand"
163            | E.Img _       => raise Fail"Img before Expand"
164            | E.Value _     => raise Fail"Value before Expand"
165                (*************Algebraic Rewrites **************)
166            | E.Neg(E.Neg e)    => rewriteBody e
167                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
168                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)          | E.Lift e          => E.Lift(rewriteBody e)
169            | E.Add es          => let
170                val (change,body')= mkAdd(List.map rewriteBody es)
171                     in if (change=1) then ( changed:=true;body') else body' end                     in if (change=1) then ( changed:=true;body') else body' end
172            | E.Sub(a, E.Field f)=> (changed:=true;E.Add[a, E.Neg(E.Field(f))])
174            | E.Sub(E.Sub(a,b),e2)          => rewriteBody (E.Sub(a,E.Add[b,e2]))
176                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
177                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)          | E.Div(e1 as E.Tensor(_,[_]),e2 as E.Tensor(_,[]))=>
178                | E.Partial _=>body                  rewriteBody (E.Prod[E.Div(E.Const 1, e2),e1])
| E.Conv (V, alpha)=> E.Conv(rewriteBody V, alpha)
| E.Probe(u,v)=>  E.Probe(rewriteBody u, rewriteBody v)
| E.Image es => E.Image(List.map rewriteBody es)
179
180                  (*Product*)          | E.Div(E.Div(a,b),E.Div(c,d))  => rewriteBody(E.Div(E.Prod[a,d],E.Prod[b,c]))
181            | E.Div(E.Div(a,b),c)           => rewriteBody (E.Div(a, E.Prod[b,c]))
182            | E.Div(a,E.Div(b,c))           => rewriteBody (E.Div(E.Prod[a,c],b))
183            | E.Div (a, b)                  => (E.Div(rewriteBody a, rewriteBody b))
184                (**************Apply, Sum, Probe**************)
185            | E.Apply(E.Partial [],e)   => e
186            | E.Apply(E.Partial d1, e1) =>
187                let
188                val e2 = rewriteBody e1
189                val (c,e3)=mkapply(E.Partial d1,e2)
190                in
191                    (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
192                end
193            | E.Apply _                 => raise Fail" Not well-formed Apply expression"
194            | E.Sum([],e)               => (changed:=true;rewriteBody e)
195            | E.Sum(c,e)                => let
196                val (c,e')=mkSum(c,rewriteBody e)
197                in
198                    (case c of 0 => e'|_ => (changed:=true;e'))
199                end
200            | E.Probe(u,v)              =>
201                let
202                val (c',b')=mkprobe(rewriteBody u,rewriteBody v)
203                in (case c'
204                    of 1=> (changed:=true;b')
205                    |_=> b'
206                    (*end case*))
207                end
208            (*************Product**************)
209            | E.Prod [] => raise Fail"missing elements in product"
210                | E.Prod [e1] => rewriteBody e1                | E.Prod [e1] => rewriteBody e1
212               (changed := true; E.Add(List.map (fn e=> E.Prod([e]@e3)) e2))
213            | E.Prod((E.Sub(e2,e3))::e4)=>
214                (changed :=true; E.Sub(E.Prod([e2]@e4), E.Prod([e3]@e4 )))
215            | E.Prod((E.Div(e2,e3))::e4)=> (changed :=true; E.Div(E.Prod([e2]@e4), e3 ))
217                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))
218                | E.Prod(e1::(E.Sub(e2,e3))::e4)=>          | E.Prod(e1::E.Sub(e2,e3)::e4)=>
219                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))                     (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))
220                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>          (*************Product EPS **************)
221                     (changed:=true;E.Conv(f,deltas@r1))
222                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>          | E.Prod(E.Epsilon(i,j,k)::E.Apply(E.Partial d,e)::es)=>let
223                     (changed:=true;              val change= G.matchEps(0,d,[],[i,j,k])
224                      let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)              in case (change,es)
225                      in e end)                  of (1,_) =>(changed:=true; E.Const 0)
226                    | (_,[]) =>E.Prod[E.Epsilon(i,j,k),rewriteBody (E.Apply(E.Partial d,e))]
227                    |(_,_)=> let
228                        val a=rewriteBody(E.Prod([E.Apply(E.Partial d,e)]@ es))
229                        val (_,b)=mkProd [E.Epsilon(i,j,k),a]
230                        in b end
231                end
232    (*
233            | E.Prod(E.Epsilon(i,j,k)::E.Conv(V1,[a1], h1, d1)::E.Conv(V,alpha, h, d)::es)=>let
234                val change= G.matchEps(0,alpha@d,[],[i,j,k])
235                in case (change,es)
236                    of (1,_) =>(changed:=true; E.Lift(E.Const 0))
237                    | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V1,[a1], h1, d1),E.Conv(V,alpha, h, d)]
238                    | (_,_) =>let
239                        val a=rewriteBody(E.Prod([E.Conv(V1,[a1], h1, d1),E.Conv(V,alpha, h, d)]@ es))
240                        val (_,b) = mkProd [E.Epsilon(i,j,k),a]
241                        in b end
242                end
243    *)
244            | E.Prod(E.Epsilon(i,j,k)::E.Conv(V,alpha, h, d)::es)=>let
245                val change= G.matchEps(0,d,[],[i,j,k])
246                in case (change,es)
247                    of (1,_) =>(changed:=true; E.Lift(E.Const 0))
248                    | (_,[]) =>E.Prod[E.Epsilon(i,j,k),E.Conv(V,alpha, h, d)]
249                    | (_,_) =>let
250                        val a=rewriteBody(E.Prod([E.Conv(V,alpha, h, d)]@ es))
251                        val (_,b) = mkProd [E.Epsilon(i,j,k),a]
252                        in b end
253                end
254                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>                | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
255                      if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))              if(e2=i1 andalso e3=i2)
256                then (changed :=true;E.Const(0))
257                      else body                      else body
258               | E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))  (*
259               | E.Prod(E.Partial r1::E.Partial r2::p)=>          | E.Prod(E.Epsilon e1::E.Sum(c1,E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es3))::es2))::es1) =>
260                     (changed:=true;E.Prod([E.Partial(r1@r2)]@p))              (case G.epsToDels([E.Epsilon e1, E.Epsilon e2]@es3@es2@es1)
261               | E.Prod [E.Partial _, _] =>body              of (1,e,sx,_,_)=> (changed:=true; E.Sum(c1@c2@sx,e))
262                | (_,_,_,_,_)=>let
263               | E.Prod (E.Partial p1::es)=> (let                      val eA=rewriteBody(E.Epsilon e1)
264                  fun prod [e1] =E.Apply(E.Partial p1,e1)                      val eB=rewriteBody(E.Prod(E.Sum(c1,E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es3))::es2))::es1))
265                  | prod(e1::e2)=(let                      val (_,e)=mkProd([eA,eB])
266                      val l= prod(e2) val m= E.Prod[e1,l]                  in
267                      val lr=e2 @[E.Apply(E.Partial p1,e1)] val(b,a) =mkProd lr                      e
end)
in (changed:=true;prod es) end)

| E.Prod(e::es)=>let
val e'=rewriteBody e
val e2=rewriteBody(E.Prod es)
val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')
|_=>mkProd [e',e2])
in b
268                     end                     end
269                (*end case*))*)
270                (*Apply*)          | E.Prod(E.Epsilon eps1::ps)=> (case (G.epsToDels(E.Epsilon eps1::ps))
271                of (1,e,[],_,_)      =>(changed:=true;e)(* Changed to Deltas *)
272                | E.Apply(E.Partial d,E.Sum(c,e))=>let              | (1,e,sx,_,_)      =>(changed:=true;E.Sum(sx,e))
273                      val(c,e')=mkApplySum(E.Apply(E.Partial d,E.Sum(c, rewriteBody e)))                      (* Changed to Deltas *)
274                  in (case c of 1=>(changed:=true;e')              | (_,_,_,_,[])   =>  body
275                      |_=> e')end              | (_,_,_,epsAll,rest) => let
| E.Apply(E.Partial [],e)=> e

| E.Apply(E.Partial p, e)=>let
val body'=E.Apply(E.Partial p, rewriteBody e)
val (c, e')=mkApply2(body')
in (case c of 1=>(changed:=true;e')
| _ =>e') end
| E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)

(* Sum *)
| E.Sum([],e)=> (changed:=true;rewriteBody e)
| E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
| E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
| E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
let val (i,e,rest)=epsToDels(body)
in (case (i, e,rest)
of (1,[e1],_) =>(changed:=true;e1)
|(0,eps,[])=>body
|(0,eps,rest)=>(let
276                              val p'=rewriteBody(E.Prod rest)                              val p'=rewriteBody(E.Prod rest)
277                              val p''= (case p' of E.Prod p=>p |e=>[e])                  val(_,b)= mkProd(epsAll@[p'])
278                              val(a,b)= mkProd (eps@p'')                  in b end
279                              in E.Sum(c,b) end              (*end case*))
280                              )          | E.Prod(E.Sum(c1,E.Prod(E.Epsilon e1::es1))::E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es) =>
281                          |_=>body)              (case G.epsToDels([E.Epsilon e1, E.Epsilon e2]@es1@es2@es)
282                    of (1,e,sx,_,_)=> (changed:=true; E.Sum(c1@c2@sx,e))
283                    | (_,_,_,_,_)=>let
284                        val eA=rewriteBody(E.Sum(c1,E.Prod(E.Epsilon e1::es1)))
285                    val eB=rewriteBody(E.Prod(E.Sum(c2,E.Prod(E.Epsilon e2::es2))::es))
286                    val (_,e)=mkProd([eA,eB])
287                    in
288                        e
289                     end                     end
| E.Sum(c, E.Prod(E.Delta d::es))=>let
val (change,a)=reduceDelta(body)
val (change',body')=(case a
of E.Prod p=> mkProd p
|_=> (0,a))
in (case change of []=>body'|_=>(changed:=true;body')) end

| E.Sum(c,E.Apply(E.Partial _,e))=>let
val (change,exp)=mkSumApply2(body)
val exp'=(case exp
of  E.Const c => E.Const c
| E.Sum(c',E.Apply(d',e'))  => (let
val s'=rewriteBody(E.Sum(c',e'))
in (case s'
of E.Sum([],e'')=>E.Apply(d',e'')
| E.Sum(s'',e'') => E.Sum(s'',E.Apply(d',e''))
| _ => E.Apply(d',s'))

end)

| _ =>exp
290                          (* end case *))                          (* end case *))
291            | E.Prod[E.Delta d, E.Neg e]=> (changed:=true;E.Neg(E.Prod[E.Delta d, e]))
292                  in (case change of 1=>(changed:=true;exp') |_=>exp')          | E.Prod(E.Delta d::es)=>let
293                val (pre',eps, dels,post)= filterGreek(E.Delta d::es)
294                 val _= testp["\n\n Reduce delta--",P.printbody(body)]
295                val (change,a)=G.reduceDelta(eps, dels, post)
296                  val _= testp["\n\n ---delta moved--",P.printbody(a)]
297                in (case (change,a)
298                    of (0, _)=> E.Prod [E.Delta d,rewriteBody(E.Prod es)]
299                    | (_, E.Prod p)=>let
300                        val (_, p') = mkProd p
301                        in (changed:=true;p') end
302                    | _ => (changed:=true;a )
303                    (*end case*))
304                end
305          | E.Prod[e1,e2]=> let
306                val (_,b)=mkProd[rewriteBody e1, rewriteBody e2]
307                in b end
308          | E.Prod(e::es)=>let
309                val e'=rewriteBody e
310                val e2=rewriteBody(E.Prod es)
311                val(_,b)=(case e2
312                    of E.Prod p'=> mkProd([e']@p')
313                    |_=>mkProd [e',e2])
314                in
315                        b
316                  end                  end

| E.Sum(c,e)=>E.Sum(c,rewriteBody e)
317
318              (*end case*))              (*end case*))
319
320        fun loop body = let      fun loop(body ,count) = let
321            val _= testp["\n\n N =>",Int.toString(count),"--",P.printbody(body)]
322              val body' = rewriteBody body              val body' = rewriteBody body
323
324              in              in
325                if !changed                if !changed
326                     then (changed := false; print " \n \t => \n \t ";print( P.printbody body');print "\n";loop body')              then  (changed := false ;loop(body',count+1))
327                  else (P.printbody(body');body')              else (body',count)
328              end              end
329      val b = loop body      val _ =testp["\n ******************* \n Start Normalize \n\n "]
330        val (b,count) = loop(body,0)
331        val _ =testp["\n Out of normalize \n",P.printbody(b),
332            "\n    Final CounterXX:",Int.toString(count),"\n\n"]
333           val xx =G.reduceDelta([],[E.Delta(E.V 2,E.V 1),E.Delta(E.V 3,E.V 0)],[E.Conv(0,[E.V 1,E.V 3],1,[E.V 0])])
334      in      in
335      ((Ein.EIN{params=params, index=index, body=b}))          (Ein.EIN{params=params, index=index, body=b},count)
336      end      end
337  end  end
338

Legend:
 Removed from v.2458 changed lines Added in v.2856